ความคาดหวังของผู้ชายต่อการเปลี่ยนแปลงบทบาทของผู้หญิงในครอบครัวในสังคมสมัยใหม่ : ศึกษากรณีกรุงเทพมหานคร - ปรารถนา ศิริศรัทธาธรรม (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The purpose of this research is to investigate man s expectation on roles of woman in the family with the main hypotheses as follows : 1. Man expects woman to play traditional roles. 2. The man s expectation on changing from traditional roles of woman will have negative impacts on the family. 3. Man expects woman to play less role outside the family. 4. Man s expectation on woman roles in the family is related to man s expectation on woman roles outside the family. Data of this research was collected by distributing the questionnaires to the sample of bachelor men in Bangkok metropolis with 264 subjects. Beside, 10 additional bachelor subjects were given in-depth interviews. The main findings of this research are: 1) Bachelor man in modern society still expects woman to play traditional role if her family have sufficient income. 2) The man still expects further that the changing role of woman from traditional one will have a negative impact on the family. 3) In addition, the man will expect the woman to play less roles outside the family. 4) The man s expectation on woman s roles in the family is related to his expectation on her roles outside the family.